Statistical abstracts of the United State 1962 - United States, Bureau of the Census; United States. Bureau of the Census; U.S. Census Bureau (Washington, DC : U.S. Dept. of Commerce, Economics and Statistics Administration, 1962)
A statistical reference and guide to over 250 statistical publications and sources from government and private organizations.
Description based on: 1995; title from print record.
Latest issue consulted: 2009 (viewed Apr. 15, 2009).
Vol. for 2004/2005 issued in a combined form.
Vols. for 1995-1997 issued by: Bureau of the Census; 1998- by: U.S. Census Bureau.
Has numerous supplements; beginning in 1993, data also available in CD-ROM publication with the same title.
Keywords: United States -- Statistics -- Periodicals; Statistiques